Enhancing IoT Security for Sustainable Development: A Parity Checking Approach for Fault Detection in PRESENT Block Cipher - Maatallah, Nada; Mestiri, Hassen; Mohamed, Abdullah Alsir; Machhout, Mohsen (Engineering, Technology & Applied Science Research, 2025)
The PRESENT lightweight block cipher designed for resource-constrained environments exhibits vulnerabilities to fault injection attacks. By deliberately introducing errors during the computation, attackers can potentially recover secret keys or bypass security measures. Various fault models, including single- and multi-bit faults targeting different stages of the cipher, have been explored, demonstrating the feasibility of such attacks. Consequently, robust countermeasures, such as error detection codes, parity checks, and hardware redundancy, are essential to enhance the fault resistance of PRESENT implementations and maintain security in real-world deployments. This paper presents an enhanced fault detection scheme for the PRESENT lightweight block cipher, designed to provide a high level of protection against a wide range of fault injection attacks. The proposed scheme focuses on detecting both simple and multiple fault attacks, addressing scenarios that target one or more bytes. A comprehensive analysis of the detection capabilities is performed, considering various fault multiplicities and injection methods. This innovative approach contributes to the advancement of secure and reliable systems, in line with the focus of SGD 9 on fostering innovation. The proposed scheme is extensively evaluated through simulations, demonstrating its ability to detect a significant percentage of injected faults. A hardware implementation on a Xilinx Virtex5-XC5VFX70T FPGA platform is explored, analyzing the trade-off between security, area, and performance. The results show that the proposed scheme achieves high fault coverage while maintaining reasonable resource utilization without impacting operating frequency. A comparison with existing techniques highlights the advantages of the proposed approach.